An integrative service operations management approach towards operations capabilities improvement: an evidence from service industries in Malaysia / Abg Hamizam Abg Mohar - Abg Mohar, Abg Hamizam (2019)
Service sector has transformed itself as one of the key driver and contributors in today's economic systems. In addition to the increasing globalisation and technological development, its complementing nature that easily transcends beyond industry has further accelerated its transformation and growth. Under this pretext, since then service providers has invested diverse range of operational practices to achieve higher operations performance. Despite an encouraging operational practices and performance relationships, direct and indirect investments in operational activities are costly and time consuming before any affect can be seen. Thus, operations managers need to know the best management approach to ensure the right investment to affect the optimum efficiency. Despite ample of studies conducted in the field, these however are overshadowed by production practices rather than services. In addition, the inherent differences between producing goods and delivering a service, and warranted a need to re-evaluate the platform as a mechanism for service operations management (SOM). Total Operations Management in Service (TOMS) is a holistic approach from the perspective of the service delivery provider in Malaysia. The approach used in the study is both qualitative and quantitative. Literatures reviews and interviews were undertaken, and further supported by multiple analysis; EFA, CFA, Multivariate test of Normality, Correlation analysis and Multiple Regression analysis. The procedures revealed seven factors of TOMS are System Delivery (SD), Human Delivery (HD), Technological Applications (TApps), Service Quality Culture (SQC), Customers Oriented Layout (COL), Service Design (Sdesign) and Employees Management (EM), which are a requirement for TOMS operating environment. This multi-factor framework illustrates the dynamic nature of SOM through which the interaction of these factors as a total provides a new perspective towards SOM by emphasizing on internal efficiency, economies of scale, cost reduction and customer satisfaction to achieve higher operations capabilities. Service operations manager would be able to better leverage internal capabilities by exploiting and manipulating relationships between factors. The determinant factors, allow the service managers to access the "right factor/s" which would reduce the chances of operational efforts to end up in failure and waste of organization resources. Specific operational investments decisions such as robotic technology, computerised manufacturing, software and quality programmes, would optimize resource utilizations and allow access to optimum operations capabilities. Under this pretext, the framework is expected to uncover neglected relationships intricacies and relevancy relationship where such potentially neglected areas. This in turn would unveil new pastures of operational practices to focus and direct their decision-making, planning and directing operational efforts towards achieving higher service operational performance. Supply chain management (SCM), which has always been important platform in operations studies to improve operations performance in manufacturing yet findings pointed out that in a service context is not a critical factor, but its associations are incorporated as items into other factors. The relationships between factors, and against operations capability, empirically suggested the need to approach SOM holistically for optimum performance. The findings reflects the departure to a more service oriented operations management.